Phthalate exposure and childhood overweight and obesity: Urinary metabolomic evidence. (December 2018) - Xia, Bin; Zhu, Qingyang; Zhao, Yingya; Ge, Wenzhen; Zhao, Yan; Song, Qi; Zhou, Yuhan; Shi, Huijing; Zhang, Yunhui
Abstract: Objective: Metabolomics may unravel global metabolic changes in response to environmental exposures and identify important biological pathways involved in the pathophysiology of childhood obesity. Phthalate has been considered an obesogen and contributing to overweight and obesity in children. The purpose of this study is to evaluate changes in urine metabolites in response to the environmental phthalate exposure among overweight or obese children, and to investigate the metabolic mechanisms involved in the obesogenic effect of phthalate on children at puberty. Methods: Within the national Puberty Timing and Health Effects in Chinese Children (PTHEC) study, 69 overweight/obese children and 80 normal weight children were selected into the current study according to their puberty timing and WGOC (The Working Group for obesity in China) references. Urinary concentrations of six phthalate monoesters (MMP, MEP, MnBP, MEHP, MEOHP and MEHHP) were measured using API 2000 electrospray triple quadrupole mass spectrometer (ESIMS/MS). Metabolomic profiling of spot urine was performed using gas chromatography-mass spectrometry. Differentially expressed urinary metabolites associated with phthalate monoesters exposure were examined using orthogonal partial least square-discriminant analysis and multiple linear regression models. In addition, the candidate metabolites were regressed to obesity indices with multiple linear regression models and logistic regression models in all subjects. Results: Compared with normal weight children, higher levels of MnBP were detected in urinary samples of children with overweight and obesity. After adjusting for confounders including chronological age, gender, puberty onset, daily energy intake and physical activity and socio-economic level, positive association remained between urinary MnBP concentration and childhood overweight/obesity [OR = 1.586, 95% CI:1.043, 2.412]. We observed elevated MnBP concentration was significantly correlated with increased levels of monostearin, 1-monopalmitin, stearic acid, itaconic acid, glycerol 3-phosphate, 5-methoxytryptamine, kyotorphin, 1-methylhydantoin, d-alanyl-d-alanine, pyrrole-2-carboxylic acid, 3, 4-Dihydroxyphenylglycol, and butyraldehyde. Meanwhile, increased MnBP concentration was also significantly correlated with decreased levels of lactate, glucose 6-phosphate, d -fructose 6-phosphate, palmitic acid, 4-acetamidobutyric acid, l-glutamic acid, n -acetyl- l -phenylalanine, iminodiacetic acid, hydroxyproline, pipecolinic acid, l-ornithine, n -acetyl-l-glutamic acid, guanosine, cytosin, and (s)-mandelic acid in the normal weight subjects. The observations indicated that MnBP exposure was related to global urine metabolic abnormalities characterized by disrupting arginine and proline metabolism and increasing oxidative stress and fatty acid reesterification. Among the metabolic markers related to MnBP exposure, 1-methylhydantoin, pyrrole-2-carboxylic acid and monostearin were found to be positively correlated with obesity indices, while hydroxyproline, l-ornithine, and lactate were negatively associated with overweight/obesity in children. Conclusions: Our results suggested that the disrupted arginine and proline metabolism associated with phthalate exposure might contribute to the development of overweight and obesity in school-age children, providing insights into the pathophysiological changes and molecular mechanisms involved in childhood obesity. Highlights: Mono-n-butyl phthalate (MnBP) exposure was significantly associated with overweight/obesity in Chinese school-age children. MnBP exposure was related to global urine metabolic abnormalities in school children of China. The disrupted arginine and proline metabolism might play an important role in mediating the putative obesogenesis of MnBP.